Renal Protective effects of Melatonin in rat treat by Gemcitabine - Pejman Mortazavi; Behnam Ahmadnezhad; Iraj Pousty; Negar Panahi; Mitra Aghazadeh; Mostafa Shalikar; Vahid Ramezani; Maryam Aghaie Meybodi (International Journal of Veterinary Science and Research - Peertechz Publications, 2017)
Nephrotoxic side effects of gemcitabine have been reported in patients receiving this drug medication. Melatonin is a potent free radical scavenger and antioxidant and has protective effects against ischemic damage. In the present study, we examined the relationship between the renal protective effects of melatonin in tubular damage induced by gemcitabine. This study was conducted simultaneously as a case of 48 male wistar rat, weighing approximately 20 ± 250 g and aged 8 weeks were used.The rats were randomly divided into 3 groups.Group 1; has found the amount of normal saline.The treatment group was divided into two sub-groups,groups, (T1) the melatonin doses 10 (mg/kg),as well as gemcitabine dose 50 (mg/kg) intraperitonealy (IP) received. (T2) the melatonin doses 20 (mg/kg),),as well as gemcitabine dose 50 (mg/kg) intraperitonealy (IP) received. The experimental group was divided into 3 sub-groups, (T3, T4, and T5). (T3); received gemcitabine with dose of 50 (mg/kg) intraperitonealy (IP). Group (T4) melatonin doses 10 (mg/kg) and (T5); melatonin doses 20 (mg/kg) and intraperitonealy (IP) received. Each group consisted of eight rat. In the group receiving only gemcitabine (T3), renal lesions were observed as tubular degeneration and necrosis. The combination of gemcitabine and melatonin reduced the renal injury. The lesions in group T5 were remarkably reduced. The results of this study shows that melatonin was effective in reducing nephrotoxicity effects of gemcitabine.